2019
DOI: 10.1186/s12985-019-1139-3
|View full text |Cite
|
Sign up to set email alerts
|

The glycoprotein, non-virion protein, and polymerase of viral hemorrhagic septicemia virus are not determinants of host-specific virulence in rainbow trout

Abstract: Background Viral hemorrhagic septicemia virus (VHSV), a fish rhabdovirus belonging to the Novirhabdovirus genus, causes severe disease and mortality in many marine and freshwater fish species worldwide. VHSV isolates are classified into four genotypes and each group is endemic to specific geographic regions in the north Atlantic and Pacific Oceans. Most viruses in the European VHSV genotype Ia are highly virulent for rainbow trout ( Oncorhynchus mykiss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…Chimeric cDNA clones and recombinant VHSV. Construction of infectious clones of the VHSV MI03 and DK-3592B strains has been described previously, and the full-length clones were designated pVHSVmi and pVHSVdk, respectively (13,50). These two parental clones were used to construct VHSV chimeric clones.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chimeric cDNA clones and recombinant VHSV. Construction of infectious clones of the VHSV MI03 and DK-3592B strains has been described previously, and the full-length clones were designated pVHSVmi and pVHSVdk, respectively (13,50). These two parental clones were used to construct VHSV chimeric clones.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting eight chimeric recombinant viruses were viable in vitro and in vivo, but they did not exhibit any change in trout virulence relative to the parental clones. Therefore, we concluded that the VHSV G, NV, and L genes, comprising 70% of the viral genome, do not contain genetic determinants of trout virulence (50).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…It differed from 559 C03MU by a single AA in the L-gene, and was found in six different fish host species and the 560 sole two known invertebrate host species [99,100]. Yusuff et al [101] discerned no effect on 561 host specificity when swapping L-genes between C03MU and Ia's DK-3592B. L variants appear 562 to differ in optimal temperature range, since swapping L from IVa into IVb led to increased virus 563 at higher temperatures, than occurred for IVa [102].…”
Section: Relationships 504mentioning
confidence: 99%